Islam and Politics in Southeast Asia edited by Johan Saravanamuttu, London: Routledge, 2010, 188 pp. - Zailan Moris (Kajian Malaysia, 2010)
Southeast Asia which is home to the largest community of Muslims in the world offers an interesting case study to scholars of Islamic studies and social scientists both for its own particular variety of understanding and practice of Islam as well as a contrast to other Muslim communities, especially that of the Islamic heartland. The event of September 11 has resulted in Islam being regarded as an enemy of the West and of America in particular, which is associated with violence and terrorism. Since September 11, there has been greater interest in the West on the study of the social, cultural and political life of Muslims in Southeast Asia in order to uncover what it perceives as a gentler and more moderate face of Islam in contrast to that of the radical and violent Middle East, Pakistan, and Afghanistan.